Study of the sea urchins (echinoidea) influence on the coral reef communities in the Nusa Dua Bali conservation area - Angellia, Vonny; Husna Nugrahapraja (Environmental and Materials, 2023)
Coral reef ecosystems are crucial for marine ecosystems as they support various other marine organisms. Sea urchins, such as Diadema setosum and Echinometra mathaei influence the coral reef communities by consuming algae that disrupt coral growth. This study aims to determine reef star coral media quantity, identify the dominant coral species at three points (BTN, Coral Garden, and Cluster 5) in Nusa Dua Beach, and assess the influence of sea urchins on coral reefs. The sampling method used was Purposive sampling, and visual observations which were conducted from June 27 to June 30, 2022. Results showed the varying sea urchin populations, with Acropora sp. and Pocillopora sp. dominating at BTN, Acropora sp. and Pectinia sp. at Coral Garden, and Acropora sp. at Cluster 5. The findings suggest that sea urchins play a key role in maintaining coral reefs by consuming macroalgae and supporting coral survival.